Ferritin Decorated PLGA/Paclitaxel Loaded Nanoparticles Endowed with an Enhanced Toxicity Toward MCF-7 Breast Tumor Cells - Turino, Ludmila Noelia (2017)
PolyLactic and Glycolic Acid nanoparticles (PLGA-NPs), coated with L-Ferritin,are exploited for the simultaneous delivery of paclitaxel and an amphiphilic Gd based MRI contrast agent into breast cancer cells (MCF7). L-Ferritin has been covalently conjugated to the external surface of PLGA-NPs exploiting NHS activated carboxylic groups. The results confirmed that nanoparticles decorated with L-Ferritin have many advantages with respect both albumin-decorated and non-decorated particles. Ferritin moieties endow PLGA-NPs with targeting capability, exploiting SCARA5 receptors overexpressed by these tumour cells, that results in an increased paclitaxel cytotoxicity. Moreover, protein coating increased nanoparticle stability thus reducing the fast and aspecific drug release before reaching the target. The theranostic potentiality of the nanoparticles has been demonstrated by evaluating the signal intensity enhancement on T1-weighted MRI images of labelled MCF7 cells. The results werecompared with that obtained with MDA cells used as negative control due to their lower SCARA5 expression.